PENDIDIKAN ISLAM DALAM TANTANGAN GLOBAL - Achmad Asrori (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
Globalization era is the reality that we ought to face it. The on going changes and some problems of education as the impact of globalization must be faced and solved as well as possible both on discourse and conmte or action polity phases. Inevitably, the islamic education will be involved and insisted to be able to give a significant contribution. This paper describes urgenry of the islamic education to reconstruct its self before, both in the institutional management, programs and learning aspects, and we must realize that the religious education has the important role in the national education system as